Analysis on the thermal response to beam impedance heating of the post LS2 proton synchrotron beam dump. (November 2019) - Teofili, L; Marongiu, M; Migliorati, M; Giordano, F; Lamas, I; Nuiry, F-X; Romagnoli, G; Salvant, B
Abstract: The High Luminosity Large Hadron Collider (HL-LHC) and the LHC-Injection Upgrade (LIU) projects at CERN are upgrading the whole CERN accelerators chain to increase beam brightness and intensity. In this scenario, some critical machine components have to be redesigned and rebuilt. Due to the increase in beam intensity, minimizing the electromagnetic interaction between the beam and devices is a crucial design task. Indeed, these interactions could lead to beam instabilities and excessive thermo-mechanical loadings in the device. In this context, this paper presents an example of multi-physics study to investigate the impedance related thermal effects. The analysis is performed on the conceptual design of the new proton synchrotron (PS) internal dump.